The prevalence and influencing factors of COVID-19 in pregnant women post-relaxation of epidemic control measures in Hunan Province, China - Yingxia Wang; Yixu Liu; Kehan Zou; Min Yang; Yinglan Wu; Donghua Xie (Frontiers in Medicine)
ObjectiveTo investigate the epidemiological characteristics of COVID-19 in pregnant women after relaxation of epidemic control measures.MethodsThis cross-sectional study employed a multistage stratified sampling method, involving six sampling sites (districts/counties) of three cities (Zhuzhou, Chenzhou, and Huaihua) in Hunan Province, China. A questionnaire-based survey collected basic maternal information, COVID-19 infection status, and pregnancy-related information of the participants. Data were extracted and double checked for accuracy. Statistical analyses were conducted using SPSS 25.0 software.ResultsAmong the 7,761 pregnant women included in the study, 5,191 (66.9%) had a positive result of SARS-CoV-2 test or related symptoms. The majority of maternal infections were mild (90.0%), and a very small fraction were severe and critical (0.4% and 0.1 %). Headache and body aches (65.3%) were the most common symptoms. Of the 5,191 pregnant women with COVID-19, 4,150 (79.9%) had no complications during pregnancy. A total of 2,711 (52.2%) infected women had deliveries, and 449 (16.6%) newborns had infections. The impacts of COVID-19 on adverse pregnancy outcomes were limited. Logistic multivariable regression analysis showed that pregnant women with an education level of junior college and above (OR = 1.39, 95% CI: 1.18, 1.64), those with a monthly household income ≥ 3,000 yuan and above (OR = 1.18, 95% CI: 1.03, 1.34), those who lived with their family during family member infection (OR = 1.48, 95% CI: 1.32, 1.66), and those with pulmonary (OR = 1.41, 95% CI: 1.07, 1.85) or other (OR = 1.40, 95% CI: 1.19, 1.65) underlying diseases were more likely to have COVID-19. A farmer/worker occupation type (OR = 0.62, 95% CI: 0.48, 0.79) was a protective factor.ConclusionA high prevalence of COVID-19 in pregnant women following relaxation of control measures has been observed at provincial scale in China. Most cases were mild, and few effects on newborns were observed. Higher education and income, living with infected family members, and having pulmonary disease were identified as risk factors, suggesting that mobility is the most critical factor influencing infection rates. This study provides useful references for epidemic prevention and control in the future.